(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: A number of Co (II), Ni (II), Cu (II), Cd (II), Au (III), and Ag (I) ligand complexes were synthesized and studied. Using 4-aminobenzonitrile and 4-methylimidazole, a novel azo ligand was designed. Mass spectra, electronic spectroscopy, molar conductance, elemental analysis (C.H.N.), magnetic measurements, 1HNMR, IR spectral investigations, and electronic spectroscopy were among the analytical techniques used to study ligand structure and their transitional metal complexes. [M(L)2Cl2] is the composition of these complexes, according to the data, where M stands for Co (II), Ni (II), Cu (II), Cd (II), and Hg (II). When M=Au (III), [MLCl2] Cl. Where M=Ag(I), we have [MLH2OCl]. A tetra hydra geometry is indicated by Ag(I) and a square planar geometry by Au (III) complex, respectively, while all other complexes have an octahedral geometry according to the complexes' electronic spectrum data and magnetic susceptibility. According to the IR data, the furthest azo nitrogen atom and the imidazole nitrogen atom serve as the co-ordination sites. The behavior of Azo ligand is bidentate. DPPH radical scavenging activity was demonstrated by the compound Au (III). The compound exhibits prospective and promising antioxidant actions, according to the results overall. Gold's anticancer properties with great efficacy, the au-complex destroys lung cancer cells while having no effect on healthy cells. This is a significant finding about the application of a gold complex as a very focused lung cancer treatment.